A chloroplast tree for Viburnum (Adoxaceae) and its implications for phylogenetic classification and character evolution1. Issue 6 (1st June 2014) - Clement, Wendy L.; Arakaki, Mónica; Sweeney, Patrick W.; Edwards, Erika J.; Donoghue, Michael J.
Abstract : Premise of the study: Despite recent progress, significant uncertainties remain concerning relationships among early‐branching lineages within Viburnum (Adoxaceae), prohibiting a new classification and hindering studies of character evolution and the increasing use of Viburnum in addressing a wide range of ecological and evolutionary questions. We hoped to resolve these issues by sequencing whole plastid genomes for representative species and combining these with molecular data previously obtained from an expanded taxon sample. Methods: We performed paired‐end Illumina sequencing of plastid genomes of 22 Viburnum species and combined these data with a 10‐gene data set to infer phylogenetic relationships for 113 species. We used the results to devise a comprehensive phylogenetic classification and to analyze the evolution of eight morphological characters that vary among early‐branching lineages. Key results: With greatly increased levels of confidence in most of the early branches, we propose a phylogenetic classification of Viburnum, providing formal phylogenetic definitions for 30 clades, including 13 with names recognized under the International Code of Nomenclature for Algae, Fungi, and Plants, eight with previously proposed informal names, and nine newly proposed names for major branches. Our parsimony reconstructions of bud structure, leaf margins, inflorescence form, ruminate endosperm, extrafloral nectaries, glandular trichomes, palisade anatomy, and pollen exine showed varying levels of homoplasy, but collectively provided morphological support for some, though not all, of the major clades. Conclusions: Our study demonstrates the value of next‐generation plastid sequencing, the ease of creating a formal phylogenetic classification, and the utility of such a system in describing patterns of character evolution.